Formation of Clusters in Mono Towns Located in Areas of Priority Socioeconomic Development; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Antonov G. D. (2017, 2017)
Title screen